Preparation method of high-performance soft magnetic powder core

By forming a nano-scale oxide coating on the surface of the amorphous magnetic powder core, the problem of unstable performance under traditional coating methods is solved, and the preparation of high-performance soft magnetic powder core is realized, reducing eddy current losses and simplifying process operations.

CN119274959APending Publication Date: 2025-01-07NBTM NEW MATERIALS GRP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411692776.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The traditional phosphoric acid passivation coating method is difficult to form a uniform and complete coating layer on the surface of the amorphous magnetic powder core, resulting in unstable performance and increased loss of the magnetic powder core, especially in the high-frequency band eddy current loss.

Method used

After nitrate is dissolved in organic solvents, silane coupling agent and ammonia water are added, the pH value is adjusted within the alkaline range, deionized water and soft magnetic powder are added to form a nano-scale oxide coating layer, and methyl acetate or carbonic acid are added. Silicone resin is added to the dimethyl ester, and after drying and heat treatment, a high-performance soft magnetic powder core is formed.

Benefits of technology

The uniform and dense coating of the soft magnetic powder core is achieved, which improves magnetic permeability and performance stability, reduces eddy current losses, improves yield and simplifies process operations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119274959A_ABST
    Figure CN119274959A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-performance soft magnetic powder core, which comprises the following steps: S1, dissolving nitrate in an organic solvent, and uniformly stirring; s2, adding a silane coupling agent, and uniformly stirring; s3, keeping the pH value in an alkaline range all the time; s4, deionized water is added into the solution obtained in the step S3, then soft magnetic powder is added, stirring is continuously conducted after the temperature is adjusted, and drying is conducted after the solution is completely evaporated; s5, carrying out preheating treatment under the protection of inert gas to prepare nanoscale oxide coated soft magnetic powder; s6, adding organic silicon resin into a methyl acetate or dimethyl carbonate solution, uniformly stirring, pouring into the coated soft magnetic powder obtained in the step S5, stirring until the solution is completely volatilized, drying, adding a lubricant, and uniformly mixing and stirring; and S7, the powder is subjected to heat treatment in the nitrogen atmosphere after being subjected to compression molding, and the high-performance soft magnetic powder core is prepared. Compared with the prior art, high performance stability and low loss are both considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soft magnetic powder cores, and in particular to a method for preparing a high-performance soft magnetic powder core. Background Art

[0002] In recent years, with the development of intelligent manufacturing, high-end communications, new energy and other industries, the requirements for device miniaturization, integration, high frequency and low loss are becoming higher and higher. Although traditional metal soft magnetic materials have high saturation magnetic induction intensity, their low resistivity leads to high eddy current loss. Even if ferrite soft magnetic materials have high resistivity, their saturation magnetic induction intensity is low, making it difficult to take into account the above requirements. Soft magnetic composite powder cores are prepared by insulating and coating magnetic particles, adding adhesives, and finally pressing and sintering. They include iron powder cores, iron silicon powder cores, iron silicon aluminum powder cores, iron nickel powder cores, iron nickel molybdenum powder cores and amorphous / nanocrystalline powder cores. Various types of powder cores play an important role in different fields due to their unique advantages.

[0003] Especially in recent years, amorphous magnetic powder cores have been developed. Compared with other types of magnetic powder cores, amorphous magnetic powder cores do not have anisotropy, grain boundaries, dislocations, etc., so they have smaller hysteresis loss and lower coercive force, lower loss and higher magnetic permeability, resistivity, and higher saturation magnetic induction intensity in the high-frequency band, and the price is moderate. Therefore, due to its unique advantages, it is widely used in consumer electronics, new energy, communications, energy storage and other fields. However, amorphous powder has high corrosion resistance, so it is difficult to form a uniform and complete coating layer on the powder surface by the traditional phosphoric acid passivation coating method, which affects the insulation effect of the particle surface, and the phosphoric acid passivation film has a poor effect in isolating eddy current losses between particles in the high-frequency band, especially the powder obtained by mechanically crushing the amorphous strip. Due to its irregular shape and sharp corners, it is very easy to cause the coating layer to break during the pressing process after phosphoric acid coating, thereby reducing the performance of the magnetic powder core. In addition, although the method of hydrolyzing tetraethyl orthosilicate to generate nano-scale silicon dioxide coating can achieve the integrity coating of amorphous magnetic powder particles, there are a large number of hydroxyl groups on the surface of the generated nano-SiO2, which easily causes further condensation reaction and leads to uneven agglomeration, and the integrity and uniformity of the amorphous magnetic powder coating cannot be achieved, resulting in instability of the soft magnetic properties of the magnetic powder core and increased loss.

[0004] Therefore, it is crucial to develop a magnetic powder core that can achieve uniform and dense coating of soft magnetic powder, especially amorphous soft magnetic powder and has excellent performance. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a high-performance soft magnetic powder core that takes into account both high performance stability and low loss in response to the above technical status quo.

[0006] The technical solution adopted by the present invention to solve the above technical problems is: a method for preparing a high-performance soft magnetic powder core, characterized in that it comprises the following steps:

[0007] S1. Dissolve nitrate in an organic solvent and stir evenly;

[0008] S2, adding a silane coupling agent to the solution obtained in step S1, and stirring evenly;

[0009] S3, adding ammonia water or sodium hydroxide solution to the solution obtained in step S2 to keep the pH value within the alkaline range;

[0010] S4, adding deionized water to the solution obtained in step S3, and then adding the sieved soft magnetic powder, adjusting the temperature and stirring continuously, and drying after the solution is completely evaporated;

[0011] S5, preheating the product obtained in step S4 under the protection of an inert gas to obtain a nano-scale oxide-coated soft magnetic powder;

[0012] S6, adding silicone resin to the methyl acetate or dimethyl carbonate solution, stirring evenly, pouring into the coated soft magnetic powder obtained in S5, stirring until the solution is completely volatilized, drying, and then adding lubricant and mixing evenly;

[0013] S7. Press the powder obtained in S6 into a shape and then perform heat treatment in a nitrogen atmosphere to obtain a high-performance soft magnetic powder core.

[0014] Preferably, in step S1, the mass ratio of nitrate to organic solvent is 1% to 30%.

[0015] Preferably, the step S1 is: after dissolving ytterbium nitrate in an organic solvent, placing it in an oil bath and stirring it evenly, the oil bath stirring temperature is 5 to 60°C, the time is 0.5 to 5 hours, and the stirring speed is 50 to 800 rpm. , the nitrate is ytterbium nitrate. Therefore, step S5 obtains a soft magnetic powder coated with nano-scale ytterbium oxide; because the ytterbium oxide coating layer has a certain paramagnetism, the magnetic permeability of the soft magnetic powder core is greatly improved.

[0016] Preferably, the silane coupling agent in step S2 is KH550, and the mass ratio of the silane coupling agent to ytterbium nitrate is (0.1-10):20; the oil bath stirring temperature in step S2 is 5-60° C., the stirring time is 0.5-5 hours; and the stirring speed is 50-500 rpm.

[0017] Preferably, in step S3, ammonia water or sodium hydroxide solution is added by slowly dropping with a separatory funnel so that the pH value of the solution is always 7 to 14; the solution is placed in an oil bath and stirred, the oil bath stirring temperature is 5 to 60° C., the oil bath stirring time is 0.5 to 10 hours, and the stirring speed is 50 to 500 rpm.

[0018] Preferably, in step S4, the ratio of the mass of deionized water to the total mass of the solution is 1% to 50%; the solution is placed in an oil bath and stirred, the oil bath stirring temperature is 60 to 300° C., and the oil bath stirring time is 0.5 to 30 hours; the stirring speed is 50 to 500 rpm; the drying is oven drying, the oven temperature is 50 to 200° C., and the drying time is 1 to 5 hours.

[0019] Preferably, in the step S4, the soft magnetic powder raw powder is sieved through a 100-500 mesh sieve to obtain the sieved soft magnetic powder, and the mass of the soft magnetic powder raw powder is 1-20 times the total mass of the solution obtained in step S3; the soft magnetic powder is one or more of carbonyl iron powder, iron silicon powder, iron silicon aluminum powder, iron nickel powder, iron silicon boron powder, iron silicon boron carbon powder, iron silicon boron carbon chromium powder, iron silicon boron carbon cobalt powder, and iron silicon boron copper niobium powder. Crushed strip powder or atomized spherical powder.

[0020] Preferably, the inert gas in step S5 is argon or nitrogen, and the preheating treatment is: after keeping warm at 100-600° C. for 0.5-5 hours, keep warm at 600-1500° C. for 0.5-10 hours.

[0021] Preferably, in step S6, the mass ratio of methyl acetate or dimethyl carbonate solution to powder is (1-50):100; the mass ratio of silicone resin to powder is (0.1-10):100; the lubricant is one of zinc stearate, calcium stearate and barium stearate, and the mass ratio of lubricant to powder is (0.3-10):100; the oven temperature is 50-300° C., and the drying time is 0.5-10 hours.

[0022] Preferably, the pressure of the press molding in step S7 is 800-2000 MPa, the holding time of the press molding is 5-200 seconds, the temperature of the heat treatment is 200-2000°C, the heat treatment time is 0.5-10 hours, and the heating rate of the heat treatment is 1-10°C / min. More preferably, the pressure of the press molding in step S7 is 1000 MPa.

[0023] The steps of the method for preparing a high-performance soft magnetic powder core of the present invention are as follows:

[0024] S1. Dissolve nitrate in an organic solvent such as acetone or alcohol, place in an oil bath and stir evenly at room temperature. The oil bath stirring temperature is 5 to 60°C for 0.5 to 5 hours. The stirring speed is 50 to 800 rpm. The mass ratio of nitrate to organic solvent is 1% to 30%.

[0025] S2. Add silane coupling agent KH550 to the solution obtained in step S1, and continue stirring at room temperature; the mass ratio of silane coupling agent to nitrate is (0.1-10):20; the oil bath stirring temperature is 5-60° C., the stirring time is 0.5-5 hours; the stirring speed is 50-500 rpm;

[0026] S3. Slowly add ammonia water or sodium hydroxide solution to the solution obtained in step S2 using a separatory funnel to keep the pH value within the alkaline range, and continue stirring at room temperature; the oil bath stirring temperature is 5 to 60° C., the oil bath stirring time is 0.5 to 10 hours, and the stirring speed is 50 to 500 rpm;

[0027] S4, add deionized water to the solution obtained in step S3, the mass of deionized water accounts for 1% to 50% of the total mass of the solution; after being completely dispersed, add the soft magnetic powder screened by 100-500 mesh screen, adjust the temperature and continue stirring, after the solution is completely evaporated, put it in an oven until it is completely dried and then take it out; the oil bath stirring temperature is 60-300°C, the oil bath stirring time is 0.5-30 hours; the stirring speed is 50-500rmp; the oven temperature is 50-200°C, and the drying time is 1-5 hours; the mass of the original soft magnetic powder is 1-20 times the total mass of the solution obtained in step S3;

[0028] S5, placing the product obtained in step S4 in a vacuum furnace, and preheating the powder under the protection of an inert gas such as argon or nitrogen to obtain a nano-scale oxide-coated soft magnetic powder; the preheating treatment is: keeping the temperature at 100-600° C. for 0.5-5 hours, and then keeping the temperature at 600-1500° C. for 0.5-10 hours;

[0029] S6, adding silicone resin to methyl acetate or dimethyl carbonate solution, stirring evenly, pouring into the coated soft magnetic powder obtained in S5, stirring until the solution is completely volatilized, putting into an oven until completely dry, taking out, and then adding lubricant to mix and stir evenly; the mass ratio of methyl acetate or dimethyl carbonate solution to powder is (1-50):100; the mass ratio of silicone resin to powder is (0.1-10):100; the lubricant is one of zinc stearate, calcium stearate, and barium stearate, and the mass ratio of lubricant to powder is (0.3-10):100; the oven temperature is 50-300°C, and the drying time is 0.5-10 hours;

[0030] S7, pressing the powder obtained in S6 into a shape, and then heat-treating the magnetic powder core in a nitrogen atmosphere to obtain the soft magnetic powder core. The pressure of the pressing is 800-2000 MPa; the holding time of the pressing is 5-200 seconds; the temperature of the heat treatment is 200-2000°C, the heat treatment time is 0.5-10 hours, and the heating rate of the heat treatment is 1-10°C / min.

[0031] Compared with the existing technology, the advantages are:

[0032] ① Select nitrate solution as the precursor, dissolve the precursor in an appropriate amount of organic solvent and add an appropriate amount of silane coupling agent, stir well and evenly to obtain a uniform solution with good adsorption characteristics, stability and dispersibility; add an appropriate amount of deionized water and continue stirring to induce the hydrolysis reaction of the precursor; then add soft magnetic powder to form a dense and uniform nano-scale oxide insulating coating layer on the surface of the powder particles, a complete and uniform coating layer, so that the performance stability of the obtained soft magnetic powder core is good;

[0033] ② The dense and uniform nano-scale oxide insulating coating layer achieves the tightness of the coating layer and the powder particles, avoiding the damage of the insulating layer during the pressing process, effectively avoiding the reduction of magnetic properties, improving the yield rate, and effectively reducing the eddy current loss of the magnetic powder core;

[0034] ③ The preparation method of the present invention is safe to operate and has a simple process. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 XRD diffraction pattern of amorphous powder used in the embodiment of the present invention;

[0036] Figure 2 This is a scanning electron microscope image of the surface morphology of the amorphous powder used in Example 1 before coating;

[0037] Figure 3 This is a scanning electron microscope image of the surface morphology of the amorphous powder used in Example 1 after coating. DETAILED DESCRIPTION

[0038] The present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0039] The soft magnetic powder selected in all embodiments and comparative examples of the present invention is amorphous powder Fe 87 Si7B 2.5 C1Cr 2.5The present invention selects amorphous powder Fe 87 Si7B 2.5 C1Cr 2.5 X-ray diffraction (XRD) test was performed, and the results were as follows Figure 1 As shown, there is an obvious steamed bun peak near 45°, which proves that the powder is amorphous. The soft magnetic powder is produced by Deqing Xinchen New Materials Co., Ltd.

[0040] Example 1

[0041] The following steps are involved:

[0042] S1. Dissolve 10 g of ytterbium nitrate in 50 g of alcohol solution, place in an oil bath and stir at 25°C for 2 hours at a stirring speed of 300 rpm.

[0043] S2. Add 0.5 g of KH550 to the solution obtained in step S1, and stir in an oil bath at 25° C. for 1 hour at a stirring speed of 300 rpm.

[0044] S3. Slowly add 20 g of aqueous ammonia to the solution obtained in step S2 using a separatory funnel, keep the above stirring conditions unchanged, and keep the pH value at 8-9.

[0045] S4. Add 10 g of deionized water to the solution obtained in step S3, keep the stirring conditions unchanged, and control the pH value to be between 8 and 9. After stirring for 1 hour, add 200 g of amorphous soft magnetic powder screened with a 200-mesh sieve, increase the oil bath temperature to 80°C, maintain the stirring speed at 300 rpm, and put the solution into an oven after it is completely evaporated. Set the oven temperature to 150°C and dry it for 1 hour until it is completely dry.

[0046] S5. Place the dried powder in a vacuum furnace and keep it at 150°C for 1 hour and then at 300°C for 3 hours under argon protection.

[0047] S6, take 2g of silicone resin and 20g of methyl acetate solution, stir evenly after mixing, after the silicone resin is completely dispersed, slowly pour the mixed solution into the powder obtained in step S5, and quickly and fully stir, put it into an oven after the methyl acetate is completely volatilized, set the temperature to 100 ° C, and dry it for 1.5 hours until it is completely dry. Take it out after drying, add 4g of zinc stearate to the powder, grind and stir for 1 hour until it is completely uniform, and obtain a mixed powder.

[0048] S7, put the mixed powder obtained in step S6 into a mold, and press it under a cold press, the pressing pressure is 1000MPa, the holding time is 10 seconds, and after the pressing is completed, the mold is demolded and taken out to obtain a ring-shaped green embryo, the outer diameter of the ring-shaped green embryo is 23.88mm, the inner diameter is 14.35mm, and the height is 8mm. Keep it in a sintering furnace for 1 hour, the sintering temperature is 450℃, the heating rate is 5℃ / min, and it is naturally cooled to room temperature after sintering to obtain the desired amorphous high-performance soft magnetic powder core.

[0049] The amorphous raw powder Fe 87 Si7B 2.5 C1Cr 2.5 The morphology was photographed using a scanning electron microscope. Figure 2 As shown, the surface is smooth and complete, and the sphericity is good. Figure 3 This is a scanning electron microscope image of the surface morphology of the amorphous powder after coating in this embodiment. A large number of nano-scale coatings are gathered on the surface, and the coating layer is uniform and dense.

[0050] Example 2

[0051] The difference between this embodiment and embodiment 1 is that: in step S1 of this embodiment, 20 g of ytterbium nitrate is dissolved in 50 g of alcohol solution; and the mass of KH550 added in step S2 is 1.0 g.

[0052] Example 3

[0053] The difference between this embodiment and embodiment 1 is that the mass of KH550 added in step S2 of this embodiment is 1.0 g; the mass of deionized water added in step S4 is 20 g.

[0054] Example 4

[0055] The difference between this embodiment and embodiment 2 is that after adding deionized water and amorphous magnetic powder in step S4 of this embodiment, the temperature of the oil bath is increased to 150° C. while the stirring speed remains unchanged, so as to shorten the hydrolysis reaction time of ytterbium nitrate.

[0056] Comparative Example 1

[0057] The difference between this comparative example and Example 1 is:

[0058] The steps S6 and S7 of the comparative example are:

[0059] S6, take 2g of silicone resin and 20g of methyl acetate solution, mix and stir evenly, after the silicone resin is completely dispersed, slowly pour the mixed solution into 200g of amorphous raw powder after sieving with a 200-mesh sieve, and stir quickly and fully, after the methyl acetate is completely volatilized, put it in an oven, set the temperature to 100°C, and dry it for 1.5 hours until it is completely dry. After drying, take it out, add 4g of zinc stearate to the powder, grind and stir for 1 hour until it is completely uniform.

[0060] S7, put the mixed powder obtained in step S6 into a mold, press it under a cold press, set the pressure to 1000MPa, hold the pressure for 10 seconds, demold and take out after pressing, the outer diameter of the annular green embryo is 23.88mm, the inner diameter is 14.35mm, and the height is 8mm. Keep it in a sintering furnace for 1 hour, the sintering temperature is 450℃, the heating rate is 5℃ / min, and it is naturally cooled to room temperature after sintering to obtain the amorphous magnetic powder core of the comparative example.

[0061] It can be seen that this comparative example does not undergo insulation coating.

[0062] The amorphous magnetic powder core prepared in the above examples and comparative examples was wound with 25 turns of inductor coil using enameled wire with a wire diameter of 0.8 mm and a wire length of 1 m. The properties of the soft magnetic powder core were measured and are shown in the following table:

[0063] Table 1 Soft magnetic powder core properties of Examples 1-4 and Comparative Examples

[0064]

[0065] As can be seen from Table 1, the loss of the soft magnetic powder core of Examples 1-4 is less than that of the comparative example, and the quality factor is greater than that of the comparative example. The quality factor represents the ratio of the energy stored in the energy storage device to the energy consumed in one cycle. The higher the quality factor, the slower the rate of energy loss of the device during resonance. Therefore, the high-performance soft magnetic powder core obtained by the method of the present invention has low loss. In addition, the DC bias characteristics of Examples 1-4 are less than that of the comparative example, and the DC bias characteristics of the obtained electronic device are good.

Claims

1. A method for preparing a high-performance soft magnetic powder core, characterized in that: The following steps are involved: S1. Dissolve nitrate in an organic solvent and stir evenly; S2, adding a silane coupling agent to the solution obtained in step S1, and stirring evenly; S3, adding ammonia water or sodium hydroxide solution to the solution obtained in step S2 to keep the pH value alkaline; S4, adding deionized water to the solution obtained in step S3, and then adding the sieved soft magnetic powder, adjusting the temperature and stirring continuously, and drying after the solution is completely evaporated; S5, preheating the product obtained in step S4 under the protection of an inert gas to obtain a nano-scale oxide-coated soft magnetic powder; S6, adding silicone resin to the methyl acetate or dimethyl carbonate solution, stirring evenly, pouring into the coated soft magnetic powder obtained in S5, stirring until the solution is completely volatilized, drying, and then adding lubricant and mixing evenly; S7. Press the powder obtained in S6 into a shape and then perform heat treatment in a nitrogen atmosphere to obtain a high-performance soft magnetic powder core.

2. The method for preparing a high-performance soft magnetic powder core according to claim 1, characterized in that: In the step S1, the mass ratio of nitrate to organic solvent is 1% to 30%.

3. The method for preparing a high-performance soft magnetic powder core according to claim 2, characterized in that: The step S1 is as follows: the nitrate is ytterbium nitrate; after dissolving ytterbium nitrate in an organic solvent, the mixture is placed in an oil bath and stirred evenly; the oil bath stirring temperature is 5 to 60° C., the stirring time is 0.5 to 5 hours; and the stirring speed is 50 to 800 rpm.

4. The method for preparing a high-performance soft magnetic powder core according to claim 1, characterized in that: The silane coupling agent in step S2 is KH550, and the mass ratio of the silane coupling agent to the nitrate is (0.1-10):20; the oil bath stirring temperature in step S2 is 5-60° C., the stirring time is 0.5-5 hours; and the stirring speed is 50-500 rpm.

5. The method for preparing a high-performance soft magnetic powder core according to claim 1, characterized in that: In step S3, ammonia water or sodium hydroxide solution is added by slowly dropping with a separatory funnel to keep the pH value of the solution at 7 to 14; the solution is placed in an oil bath and stirred, the oil bath stirring temperature is 5 to 60° C., the oil bath stirring time is 0.5 to 10 hours, and the stirring speed is 50 to 500 rpm.

6. The method for preparing a high performance soft magnetic powder core according to claim 1, characterized in that: In the step S4, the mass of deionized water accounts for 1% to 50% of the total mass of the solution; the solution is placed in an oil bath and stirred, the oil bath stirring temperature is 60 to 300° C., the oil bath stirring time is 0.5 to 30 hours; the stirring speed is 50 to 500 rpm; the drying is oven drying, the oven temperature is 50 to 200° C., and the drying time is 1 to 5 hours.

7. The method for preparing a high-performance soft magnetic powder core according to claim 6, characterized in that: In the step S4, the soft magnetic powder raw powder is sieved through a 100-500 mesh sieve to obtain the sieved soft magnetic powder, and the mass of the soft magnetic powder raw powder is 1-20 times the total mass of the solution obtained in step S3; the soft magnetic powder is one or more of carbonyl iron powder, iron silicon powder, iron silicon aluminum powder, iron nickel powder, iron silicon boron powder, iron silicon boron carbon powder, iron silicon boron carbon chromium powder, iron silicon boron carbon cobalt powder, and iron silicon boron copper niobium powder. Crushed strip powder or atomized spherical powder.

8. The method for preparing a high-performance soft magnetic powder core according to any one of claims 1 to 7, characterized in that: In step S5, the inert gas is argon or nitrogen, and the preheating treatment is: after keeping the temperature at 100-600° C. for 0.5-5 hours, keep the temperature at 600-1500° C. for 0.5-10 hours.

9. The method for preparing a high performance soft magnetic powder core according to any one of claims 1 to 7, characterized in that: In step S6, the mass ratio of methyl acetate or dimethyl carbonate solution to powder is (1-50):100; the mass ratio of silicone resin to powder is (0.1-10):100; the lubricant is one of zinc stearate, calcium stearate, and barium stearate, and the mass ratio of lubricant to powder is (0.3-10):100; the oven temperature is 50-300° C., and the drying time is 0.5-10 hours.

10. The method for preparing a high performance soft magnetic powder core according to any one of claims 1 to 7, characterized in that: The pressure of the pressing in step S7 is 800-2000 MPa; the holding time of the pressing is 5-200 seconds; the temperature of the heat treatment is 200-2000°C, the heat treatment time is 0.5-10 hours, and the heating rate of the heat treatment is 1-10°C / min.